Analysis of the Modern Methods and Means for Rapid Toxin Indication - V. G. Germanchuk; D. V. Utkin; S. A. Shcherbakova (Проблемы особо опасных инфекций, 2012)
The risk of occurrence of emergency situations different in their character is still a pressing issue for all the states of the world's community, including the Russian Federation. Nowadays, development of the modern methods and tools for rapid toxin detection and identification holds a high position in biological safety system. Specified means for biological toxin detection do not comply with the requirements of rapidness. One of the prospective means for rapid toxin indication is immune-chromatographic, immunochip, and immunosensor test-systems with high sensitivity, differentiation capacity and expression. In this review described are some up-to-date foreign and home-grown technologies for rapid toxin indication.